Pedagogical knowledge and skill competences of pre-school teachers in Ibadan metropolis, Oyo State, Nigeria (2015)
Early childhood educators are faced with many important tasks in their day to day activities which include caring, stimulating, and instructing for young learners. The implementation of these tasks require certain competences which the teachers must possess in order to be effective in discharging their duties and to provide for quality early childhood education. It has been observed that with respect to the pedagogical knowledge and skill competences, teachers of young learners still have a long way to go in learning how to handle young children especially in the way they relate curriculum content to children’s needs and experiences, integrate content across learning areas, and use of child-friendly approaches, methods, and techniques in teaching. The study adopted a descriptive survey design. The sample involved in the study comprised 58 pre-school teachers randomly sampled from pre-primary section of public primary schools in the five local government areas within Ibadan city. Two research questions were set to guide the study, and one self-designed and validated rating scale on pre-school teachers’ pedagogical knowledge and skill (r-0.48) was used to gather the data. The data were analyzed by using frequency count, percentage, mean, and standard deviation. The results showed that the level of pedagogical knowledge and skill competences displayed by the pre-school teachers was low. Recommendations were made by suggesting strategies that could develop the pedagogical knowledge and skill competences of pre-school teachers for quality early childhood education.